2019
DOI: 10.4041/kjod.2019.49.3.150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of changing various parameters in miniscrew-assisted rapid palatal expansion: A three-dimensional finite element analysis

Abstract: Objective This study aimed to analyze the effect of changing various parameters of the bone-borne rapid palatal expander (RPE) using the finite element method (FEM). Methods In eight experimental groups, we investigated the effect of the number, position, and length of miniscrews; positional changes of the expander; and changes in the hook length on maxillary expansion. In finite element analysis, we compared the magnitude and distribution of stress, and the displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Taken together with the current literature, our findings suggest that the anterior region of the palate is the most appropriate insertion site owing to the high success rate and ideal anatomical characteristics. 53 - 56 However, unintentional injuries to the roots of the anterior teeth were reported in 2 studies. 16 , 27 In these studies, root damage occurred because of improper positioning, with the placement of the miniscrews at the second palatine rugae or ahead.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together with the current literature, our findings suggest that the anterior region of the palate is the most appropriate insertion site owing to the high success rate and ideal anatomical characteristics. 53 - 56 However, unintentional injuries to the roots of the anterior teeth were reported in 2 studies. 16 , 27 In these studies, root damage occurred because of improper positioning, with the placement of the miniscrews at the second palatine rugae or ahead.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing the results with finite element model (FEM), the zygomaxillary suturein a human model represented a important stress zone in all micro‐implant position and length 35 . Moreover, sagittal displacement of the maxilla was dependent of micro‐implant position and length and may present positive or negative values (compression or traction) 35 .…”
Section: Discussionmentioning
confidence: 94%
“…32,33 The MPS was the only disarticulated suture after activations in this experiment, with a mean tension value of 5639.16 με, ( Comparing the results with finite element model (FEM), the zygomaxillary suturein a human model represented a important stress zone in all micro-implant position and length. 35 Moreover, sagittal displacement of the maxilla was dependent of micro-implant position and length and may present positive or negative values (compression or traction). 35 In a second human FEM study, it was observed more stress and displacement in the maxilla-zygomatic suture then maxilla pterygoid-process suture, 36 these results were very similar in this research.…”
Section: Ta B L E 4 Median Values (Interquartile Deviation) Of Mps Deformation (με) After All Activations In Each Animalmentioning
confidence: 99%
“…Additionally, a previous FEM study identified that, in terms of stress distribution and transverse displacement, four mini-implants are preferable. 17 …”
Section: Discussionmentioning
confidence: 99%